Stress của giáo viên dạy trẻ khuyết tật tại các cơ sở giáo dục trên địa bàn tỉnh Tây Ninh - Võ, Kim Tuyết; Nguyễn, Thị Ngọc Bé (Tạp chí Giáo dục, 2025)
Teachers of children with disabilities often face difficulties in dealing with children’s unique behaviours. If prolonged over time, this situation will lead to burnout and lack of motivation at work, thereby negatively affecting the quality of teaching and children’s development. The article investigates the current stress situation of teachers of children with disabilities in educational institutions in Tay Ninh province with 136 teachers participating in the survey, the proportion of women accounting for 80.1% and men accounting for 19.9%. The research results show that the majority of preschool teachers (94.1%) are not stressed, and 5.9% of teachers are at a mild level of stress. The research results show no difference in the stress level between men and women, but there is a difference between seniority and professional qualifications. These findings highlight the need for preventive and psychological support programs to reduce stress and improve mental health for teachers of children with disabilities.